2001
DOI: 10.1016/s0550-3213(01)00217-6
|View full text |Cite
|
Sign up to set email alerts
|

Gauge invariant Z(2) vortex vacuum textures and the SU(2) gluon condensate

Abstract: For SU (2) lattice gauge theory, a new SO(3) cooling procedure is proposed which removes the SU (2)/Z(2) coset fields from the lattice configurations and reveals a Z(2) vortex vacuum texture different from the P -vortex content obtained in the maximal center gauge. Cooling can be restricted in a renormalization group invariant way by a parameter controlling the remaining SO(3) action density. A gauge invariant Z(2) vortex vacuum emerges asymptotically if cooling is not restricted. This "vortex texture" does no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…For rating the phenomenological importance of these, say, c-vortices, center dominance of the string tension was verified. In addition, the SU(2) action density which is carried by the c-vortex vacuum texture properly extrapolates to the continuum limit and, hence, gives rise to a mass dimension four condensate which features in the operator product expansion [13].…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…For rating the phenomenological importance of these, say, c-vortices, center dominance of the string tension was verified. In addition, the SU(2) action density which is carried by the c-vortex vacuum texture properly extrapolates to the continuum limit and, hence, gives rise to a mass dimension four condensate which features in the operator product expansion [13].…”
mentioning
confidence: 79%
“…In addition, it was observed that the vortex properties are quite sensitive to the finite size of the lattice volume [12]. For avoiding the practical Gribov and related problems, a gauge invariant definition of the vortex vacuum texture was achieved by employing a new self-restricted cooling procedure which diminishes the coset fields while leaving the center degrees of freedom un-changed [13]. For rating the phenomenological importance of these, say, c-vortices, center dominance of the string tension was verified.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In practice, this subtraction uses the result of a high order calculation in lattice perturbation theory [2]. Alternatively, the gluon contribution can be removed by a cooling procedure which reduces the action of the coset (gluon) fields A µ (x) [1]. The latter approach suggests that the gluon condensate G gets contributions from the energy density stored in the underlying Z 2 fields, which are revealed by the coset cooling mechanism.…”
Section: The Finite Temperature Gluon Condensatementioning
confidence: 99%